Calculation of Flood Recurrence of Delibekirli Basin (Kırıkhan/Hatay) using Statistical and Deterministic Methods and Modeling with HEC-RAS - Mahsum Bozdoğan; Ergin Canpolat (Doğal Afetler ve Çevre Dergisi)
As an inevitable consequence of population growth, human beings occupying more space on the earth's surface are more likely to encounter and be damaged by natural events. In order to minimize these damages, planning is required. Risk modelling studies are an important parameter in planning. Models can be made with higher accuracy with the help of Geographic Information Systems (GIS) and Remote Sensing (RS) technologies, which have been used intensively in multidisciplinary fields in recent years. In this study, the flood risk potential of the Delibekirli Stream Basin, which is located in the central part of the Amanos Mountains and has flood records in 2014 and 2015, was revealed by statistical and deterministic methods. Using various statistical parameters and distribution functions, the unit hydrograph peak flow and 2, 5, 10, 25, 50, 100, 500 and 1000-year flood recurrence flows of the basin were calculated. Using these values, a 1D hydraulic model was created in steady flow conditions using the River Analysis System (HEC-RAS v.6.1) software developed by the US Army Corps of Engineers, Hydrologic Engineering Center (USACE-HEC). In the city of Kırıkhan, which was built on the accumulation fan formed by the Delibekirli Stream, the channel cross-sections were narrowed due to the construction and various interventions were made to the river bed. As a result of the studies and evaluations carried out, it was concluded that in order to prevent the floods that may occur due to the Delibekirli Stream in Kırıkhan from causing loss of life and property, it was concluded that the works for the river channel should be designed based on at least 500-year flood flow (124,36 m3/s).